Restriction Of Fetal Growth - Ayala-Peralta, Félix (2017)
Fetal growth restriction (RCF) is a clinical circumstance in which the fetus does not express its genetic potential for growth and as a final result a decrease in body weight occurs, which is below the 10th percentile for gestational age, in a selected growth curve. Among the etiological factors include: maternal, fetal and placental causes. It is classified as Precocious and late. The appropriate time for delivery is determined by gestational age and fetal condition.